Analisis Kebutuhan Pengembangan E-Modul Dengan Mengintegrasikan Nilai IMTAQ Pada Pelajaran Biologi Siswa Kelas XI SMA Negeri 5 Pekanbaru - Selvi Rahma Yulita; Siti Robiah; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the need for the development of a Biology e-module integrated with the values ​​of Faith and Piety (IMTAQ) for grade XI students of SMA Negeri 5 Pekanbaru. This study uses a descriptive method with a qualitative approach. The subjects of the study consisted of 33 grade XI students and one Biology teacher. Data were collected through closed questionnaires and interviews. Data analysis was carried out using descriptive statistics percentages for questionnaires and content analysis of the interview results. The results showed that the need for teaching materials (78.48%), the need for the use of e-modules (78.79%), and the integration of IMTAQ values ​​(79.09%) were in the need category, while the student expectation indicator obtained the highest percentage of 82.88% with the very need category. These findings indicate that the development of an IMTAQ-integrated Biology e-module is urgently needed as an innovative learning medium to increase learning motivation, independence and the formation of students' religious character.